Pengaruh Stress Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan: Studi Kasus Pendidik Dan Tenaga Kependidikan SDN 038 Kiaracondong, Kota Bandung - Putri, Defina Fitriana; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the extent to which work stress and job satisfaction influence the daily performance of employees, with the research object being teachers and education staff at SD Negeri 038 Kiaracondong, Bandung. The research employed a quantitative approach using a total sampling technique that involved 30 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results show that work stress does not significantly affect performance when tested partially, as indicated by a t-value smaller than the t-table (0.918 < 1.701) with a significance level of 0.367. Conversely, job satisfaction demonstrates a strong positive influence on employee performance, with a t-value of 8.454 exceeding the t-table value of 1.701 and a significance level of 0.000. The simultaneous test (F-test) indicates that both variables collectively affect performance, with an F-value of 40.033 greater than the F-table value of 3.35. The coefficient of determination (R²) is 0.739, meaning that work stress and job satisfaction together explain 73.9% of the variance in employee performance. These findings highlight the crucial role of enhancing job satisfaction as the primary factor in improving the performance of teachers and education staff in schools.